The Influence of Good Corporate Governance on Financial Performance in Private Education Sector Business Agencies in South Tangerang, Banten - Supatmin, Supatmin (International Journal of Social Science and Business, 2025)
The increase in business opportunities in the education sector has resulted in very high competition in this sector. Based on these reasons, it is important to examine the influence of Good Corporate Governance (GCG) on financial performance in private educational sector business institutions, especially in private educational institutions in South Jakarta. This study aims to analyze the impact of Good Corporate Governance (GCG) on financial performance in private educational institutions in South Tangerang, Banten. The independent variables in this study include the independent board of commissioners, board of directors, audit committee, managerial ownership, and institutional ownership, while the dependent variable is financial performance.  The study was conducted on 30 private schools, consisting of 10 elementary schools, 10 junior high schools, and 10 senior high schools. The research method employs multiple linear regression analysis, with data processing conducted using SPSS. The results indicate that the board of directors and institutional ownership variables have a positive and significant impact on financial performance. Conversely, the independent board of commissioners, audit committee, and managerial ownership variables do not significantly affect financial performance. These findings suggest that strengthening the role of the board of directors and institutional ownership can enhance the financial performance of private educational institutions.